Think when you see one, give thanks when you see one - Ismoilova Malika Ismoilovna (Academia One Publishing, 2024)
This article will talk about ingratitude, about living Thanksgiving, as well as about its place and importance in our current life
Keywords: gratitude; adornment; ingratitude; thanks